2020
DOI: 10.1016/s2214-109x(20)30282-5
|View full text |Cite
|
Sign up to set email alerts
|

Rohingya refugees at high risk of COVID-19 in Bangladesh

Abstract: workers, it might not be possible to provide adequate services to the refugees without increasing the risk of SARS-CoV-2 infection; health-care workers are at the most risk of contracting SARS-CoV-2. 8 Limited financial aids and overcrowded and unhealthy living conditions can make their situation worse. 9 A study from May 2020, showed that COVID-19 symptoms are highly prevalent in Cox's Bazar, especially in refugee camps. 4 Another study from June, 2020, showed that a largescale outbreak is likely to happen af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…Given that there are limited testing facilities in the camps, the number of COVID-19 positive cases among Rohingya refugees may be higher than reported [20,21].…”
Section: Epidemiological Pattern and Transmission Of Covid-19mentioning
confidence: 87%
See 3 more Smart Citations
“…Given that there are limited testing facilities in the camps, the number of COVID-19 positive cases among Rohingya refugees may be higher than reported [20,21].…”
Section: Epidemiological Pattern and Transmission Of Covid-19mentioning
confidence: 87%
“…They are also stigmatized by society in general and by healthcare workers in particular [23]. Stigmatization and discrimination can increase camp dwellers mental health challenges, including post-traumatic stress disorder, anxiety and stress [21]. Moreover, the stigmatization and discrimination experienced by camp-dwellers can adversely impact their healthcare-seeking behaviors, which has negative implications for the transmission of COVID-19 [26].…”
Section: Mental Health Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Modelling from a Papua New Guinean setting has demonstrated that physical distancing measures in that community were 60-70% less effective compared with Australia. 11 Public health responses across the region have already been complicated by extreme weather events and humanitarian crises. Examples include Cyclone Harold, a category 5 cyclone that recently affected the South Pacific, and the climbing infection rate in the worlds' largest refugee camp at Cox's Bazar in Bangladesh.…”
Section: Challenges In Public Health Responsementioning
confidence: 99%